Tayma, Saudi-Arabien: Multidisziplinäre Forschungen in der Oase - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2023)
Multidisciplinary research at the oasis of Tayma, Northwest Arabia, aimed at further investigating the ancient settlement in its environmental context. A special focus has been set on the palaeohydrology of the oasis as well as on the exploration of its geoarchives in the light of climatic changes. As to the settlement remains, in addition to well known vestiges from the Early Iron Age to the Early Byzantine period, remarkable progress was made in exploring earlier periods of occupation. Tayma, as one of the major oases in the region, appears to have been much more important than previously thought, implying a cultural and political autonomy which can be held responsible for far reaching contacts far before the 1st millennium BC.